Soft Graphoepitaxy for Large Area Directed Self‐Assembly of Polystyrene‐block‐Poly(dimethylsiloxane) Block Copolymer on Nanopatterned POSS Substrates Fabricated by Nanoimprint Lithography. (27th April 2015) - Borah, Dipu; Rasappa, Sozaraj; Salaun, Mathieu; Zellsman, Marc; Lorret, Olivier; Liontos, George; Ntetsikas, Konstantinos; Avgeropoulos, Apostolos; Morris, Michael A.
Abstract : Polyhedral oligomeric silsequioxane (POSS) derivatives have been successfully employed as substrates for graphoepitaxial directed self‐assembly (DSA) of block copolymers (BCPs). Tailored POSS materials of tuned surface chemistry are subject to nanoimprint lithography (NIL) resulting in topographically patterned substrates with dimensions commensurate with the BCP block length. A cylinder forming polystyrene‐ block ‐polydimethylsiloxane (PS‐ b ‐PDMS) BCP is synthesized by sequential living anionic polymerization of styrene and hexamethylcyclotrisiloxane. The patterned POSS materials provide a surface chemistry and topography for DSA of this BCP and after solvent annealing the BCP shows well‐ordered microphase segregation. The orientation of the PDMS cylinders to the substrate plane could be controlled within the trench walls by the choice of the POSS materials. The BCP patterns are successfully used as on‐chip etch mask to transfer the pattern to underlying silicon substrate. This soft graphoepitaxy method shows highly promising results as a means to generate lithographic quality patterns by nonconventional methods and could be applied to both hard and soft substrates. The methodology might have application in several fields including device and interconnect fabrication, nanoimprint lithography stamp production, nanofluidic devices, lab‐on‐chip, or in other technologies requiring simple nanodimensional patterns. Abstract : A methodology for fabricating highly ordered silicon nanostructures at a substrate is reported using nanoimprint lithography imprinted polyhedral oligomeric silsequioxane (POSS) substrates for graphoepitaxial directed self‐assembly (DSA) of block copolymer (BCP). The patterned POSS materials provide a surface chemistry and topography for DSA of a cylinder forming polystyrene‐ block ‐polydimethylsiloxane BCP with well‐ordered microphase segregation upon solvent annealing.